IMPROVING WORK READINESS ON GRADUATES: THE ROLES OF PSYCHOLOGICAL CAPITAL - Dewi, Rizqi Kurnianing; Rejeki, Asri; Fitri Sholichah, Ima (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
The challenge that is often faced in today's working world is the mismatch between the requirements demanded by the company and the competencies of the graduates. When the company conducts recruitment, many graduates are found immature and unprepared for the job, which makes difficult for graduates to be absorbed by large companies, both nationally and internationally. Therefore, graduates need to develop certain capacities beyond their competencies that will enable them to cope with the challenge in the workplace. The aim of this study is to examine how psychological capital affects on work readiness using a sample of 58 graduates in Gresik. This study uses quantitative methods. Data collection methods using the Work Readiness Scale and Psychological Capital Questionnaire. The data analysis used IBM SPSS Statistics 25 program with Simple Linear Regression technique to test the minor hypothesis and Multiple Linear Regression to test the major hypothesis. The results indicate that psychological capital has a significant effect on work readiness and does not have a partial effect. The article concludes by offering implications of the findings for graduates as well as for psychology industry and organization related to work readiness and psychological capital. The number of respondents in this study was not much, so there is a limitations in describing the actual situation. Therefore, it is hoped that further research will be able to use a wider population and sample so that it can be expected that the research results will be better.